Study on mechanism of elemene reversing tumor multidrug resistance based on luminescence pharmacokinetics in tumor cells in vitro and in vivo. Issue 57 (21st September 2020) - Chen, Liying; Chen, Zhi; Zheng, Shuang; Fan, Luhui; Zhu, Lixin; Yu, Jiandong; Tang, Chaoyuan; Liu, Qi; Xiong, Yang
Abstract : The correlation between efflux functionality of ATP-binding cassette transporters and tumor multidrug resistance reversing via elemene was investigated using bioluminescence imaging (BLI) technology and luciferase reporter gene technology. Abstract : While elemene (ELE) can reverse tumor multidrug resistance (MDR), the mechanisms for ELE reversing MDR remain unclear. Numerous studies have suggested that the efflux functionality of ATP-binding cassette (ABC) transporters, not their quantity, is more relevant to tumor MDR. However, no appropriate methods exist for real-time detection of the intracellular drug efflux caused by ABC transporters in vitro, especially in vivo, which hinders the examination of MDR reversal mechanisms. This study directly investigates the correlation between efflux functionality of ABC transporters and MDR reversal via ELE, using d -luciferin potassium salt (d -luc) as the chemotherapeutic substitute to study the intracellular drug efflux. Here, a luciferase reporter assay system combined with bioluminescence imaging confirmed that the efflux of d -luc from MCF-7/DOX Fluc cells in vitro and in vivo was significantly reduced by ELE and when combined with Doxorubicin (DOX), ELE showed a synergistically anti-tumor effect in vitro and in vivo . Additionally, the luminescence pharmacokinetics of d -luc in MCF-7/DOX Fluc cells and pharmacodynamics of the combined ELE and DOX in vivo showed a great correlation, implying that d -luc might be used as a probe to study ABC transporters-mediated efflux in order to explore mechanisms of traditional Chinese medicines reversing MDR.